Numbers, tables and statistics - Møllersen, Kajsa (2021)
The old “Lofoten Post” building sits at the end of the dock in Svolvær as an empty shell, ready for the winter storms to seal its destiny. Everything that reminds of newspaper production is stripped from the building, only dents from the editor’s desk can still be seen on the floor. Wait! A stack of newspapers, filled with tables of fishery, trade, crimes, and everything else that transforms small coastal societies from January to April every year, when the Atlantic Cod comes to spawn in Lofoten. Numbers and tables, tables and numbers. The stack is not left over from the glory days of Lofotposten , but a fresh newspaper printed as part of Lofoten International Art Festival (LIAF) 2019, and the whole building is filled with contemporary art. I have been invited to participate with a talk for the session “Maths, matter & body”, followed by a conversation with Toril Johannessen, one of the artists. Her contribution to the main exhibition is works from “Words and Years” (2010-16), a series of graphs based on data from scientific journals and news magazines. The graphs are lovely to look at, their colours are pleasing, the paper they are printed on is thick, almost like cardboard. The information they provide is funny, sometimes sad, and surprisingly interesting. My thoughts go to Florence Nightingale - nurse-statistician with beautiful graphs. My contribution to LIAF is not numbers and tables or coloured graphs - but the most beautiful part of statistics; mathematics. In my position at the Faculty of health sciences, I do a lot of teaching to students that have weak mathematical background, and have a sincere and deep fear for both proper and complex fractions. I teach statistics without mathematics, not to loose my students into despair and hopelessness. At LIAF, I’m hoping to meet an audience that are curious and comfortable with what they don’t understand, and with a sense of aesthetics in general that can open the door into mathematical beauty. I open my talk with a picture of a Mandelbrot set, all beautiful ...